Exploiting Issatchenkia orientalis SD108 for succinic acid production - Xiao, Han (Microb Cell Fact, 2014)
BACKGROUND: Recent advances in synthesizing valuable chemicals such as organic acids from low-cost renewable biomass through microbial fermentation have attracted great attention. However, the toxicity of organic acids presents a key challenge to the development of an economically viable fermentation process. Therefore, a platform organism that not only produces organic acids but also tolerates the associated toxicity is highly desirable. RESULTS: Here we report the discovery, characterization, and engineering of a yeast strain, Issatchenkia orientalis SD108, that is tolerant to low pH and high concentration of organic acids. This strain demonstrated a higher tolerance compared to I. orientalis ATCC 24210 and Classic Distiller’s Turbo yeast. In order to explore SD108 as a potential platform organism for organic acid production, we determined its draft genome sequence and use the sequencing information to guide pathway design. As proof of concept, an engineered four-gene expression cassette related to the reductive TCA cycle was assembled and integrated into the genome of a uracil auxotroph of SD108. The resulting strain was able to produce succinic acid with a titer of 11.63 g/L, yield of 0.12 g/g, and productivity of 0.11 g/L · h in batch cultures using shake flasks. CONCLUSIONS: The high tolerance of I. orientalis SD108 towards multiple important organic acids makes it a highly attractive organism as a platform host for producing this group of compounds as it will reduce production cost, facilitate downstream processing, and serve as a host for construction of production strains with both pH and specific anion tolerance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-014-0121-4) contains supplementary material, which is available to authorized users.